Leonardo pop-ups - McCarthy, Courtney Watson (London, England Thames & Hudson Ltd, 2019)
"Leonardo da Vinci (1452–1519) was a painter, architect, inventor and student of all things scientific. His natural genius crossed so many disciplines that he epitomized the term ‘Renaissance man’. Today he remains best known for his art, including two paintings that remain among the world’s most famous and admired, Mona Lisa and The Last Supper. This book features six meticulously crafted pop-ups of his most famous works: Self portrait; Annunciation; Ornithopter; Virgin & Child; Architecture – an overview of his drawings and designs; and Vitruvian Man. "--
Includes bibliographical references
Keywords: Leonardo, da Vinci -- 1452-1519.; Pop-up books -- Specimens